The Effect of Anxiety Level on Speaking Ability: Psycholinguistic Analysis - istihayyu buansari; Maulani Pangestu; Fiza Asri Fauziah Habibah (Universitas Nasional, 2023)
Psycholinguistics has contributed to numerous theories that explain how a person acquires language, produces and uses spoken and written language. Without adequate English language skills, BSI students will face fundamental problems in their studies, especially in class discussions. A descriptive study was conducted to describe the problems faced by Bina Sarana Informatika (BSI) students during class discussions. This study uses a qualitative method design. A total of 3 students who took part in this study were from the BSI English Department. This study collected data using semi-structured interviews. From the results of the research conducted, there were findings of several causes of mistakes made when students were talking, including children who feels anxious when speaking during discussions. Elements of this error can be classified based on the realm of psychology. The causes of mistakes that have feelings of anxiety and worry are related to the affective domain.